Issues relating to goodwill valuation : evidence from companies in Federation of Bosnia and Herzegovina - Gadžo, Amra (Array, 2021)
According to both theoretical and empirical research results, this paper has the aim to determine, the extent to which the current accounting regulatory framework (IFRS 3 and IAS 36) offers an adequate basis for correct valuation of goodwill. We have researched all the available critical reviews of the accounting treatment of goodwill and the quality of applying accounting regulations onto expression of the goodwill position in BH companies" practices. The empirical research was conducted on all the companies in the Federation of Bosnia and Herzegovina (FBiH), which recorded goodwill in their balance sheets in the period from 2013 to 2018. The research results have shown a high level of subjectivity in the process of determining the value of goodwill, and great discrepancies in adhering to the accounting regulations in the part of additional valuation and expression of goodwill value in financial reports. This resulted in the fact that the share of companies in FBiH which express decreased values of goodwill is far greater than the share of companies in the European union (EU). The main contribution of this paper is the fact that this is the first comprehensive research on evaluation of goodwill in FBiH companies in comparison to the situation in the EU. Also, it confirms the Agency Theory and shows great subjectivity in evaluation which results in an unjustified expression of a higher operative success in financial reports.